New Fuzzy Implication Model Consisting Only of Basic Logical Fuzzy Connectives - Stefanos Makariadis; Eleftherios Makariadis; Avrilia Konguetsof; Basil Papadopoulos (Axioms)
Fuzzy implication models play a crucial role in the field of fuzzy logic. The reason behind this reality is the fact that fuzzy implications are influenced by the properties of the model used for their creation. The importance of the mentioned models increases due to the fact that there is a need for new fuzzy implications for use in artificial intelligence and other applications. So, this paper aims to resolve this problem by creating a new model. This model, named (S,T,N) by the authors, is an evolution from previous models as it utilizes all of the basic logical fuzzy connectives in a new composition that emphasizes the use of as many connectives as practically possible. Moreover, a computer program has been developed to display various interpretations of the proposed model and allow the readers to form a deeper understanding of the paper’s research. The results provided by the research conducted are mainly due to the development of the new fuzzy implication model and, secondarily, the new tool for displaying the capabilities of the implication model. Finally, the conclusions drawn from the paper proved that the search for new fuzzy implications should not only be targeted at new research directions but also at more established ones. Furthermore, the program displayed the strong capabilities of computer-assisted computations since it allowed for rapid checking of multiple implications, thus easing the researcher’s task of practically verifying the new model’s validity.